Mrs. Ruhlin Goes to Washington: Louise Ruhlin, School Prayer, and the Possibilities and Limitations of Religious Political Lobbying in Modern America - Haberman, Aaron L. (A journal of church and state, 2009)
One day in the late 1960s, a housewife from Cuyahoga Falls, Ohio, named Louise Ruhlin had what she considered a disturbing conversation with her youngest son af